Cartagena de Indias. Urban dynamics of gentrification from its historic center (2022)
Processes of gentrification can be seen in the historic center of Cartagena de Indias, which arise from the colonial city and the republican capital, suitable as a military fort, maritime port, railway station and cultural district. This led to the occupation of the peripheral areas and the displacement of the people wholived there to give way to walls, urban walkways, railway lines and motorized avenues. The objective of the text is to describe the processes of the urban transformation of the peripheralareas of Cartagena to consolidate the fort-city, adapted as a historic center and tourist district. To this end, the historicalmethod is used of contrasting printed documental evidence with articles and studies on urban policies that allow the recognition of four periods of geodemographic changes. In conclusion, the current historic center has experienced the processes of theexpansion of the dominant classes into the lands occupied by the popular sectors, combined with the construction of roads, the protection of walls and bulwarks, the urbanization of the nearby islands and beaches for touristic ends, as well as the sociocultural expulsion of the poorer classes from the popular sectors towards faraway places, invisible and distant from the tourists.